Modern commodity futures trading - Gold, Gerald (Commodity Research Bureau Jersey CityUS, 1975)
Explains the techniques and methods for successful trading in the commodity markets. Discusses the fundamentals of trading including the origins and development of commodity exchanges; the mechanisms of futures trading; understanding the commodity quotation board; futures contract, and the clearing house facility. Highlights sources of commodity information and factors that cause change in commodity prices. Describes the federal government's commodity support program. Discusses the theory, practice, and procedures of hedging, and the various aspects of chart trading. Outlines the role of the speculator and rules for speculative trading.